Hotel Customer Segmentation for Marketing Strategy Optimization Using CRAF Framework - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi, 2024)
This research explores the implementation of the Customer Reviews and Analysis Framework (CRAF) as a crucial tool for optimizing marketing strategies in the hospitality industry. By conducting thorough data analysis and sentiment evaluation, CRAF provides valuable insights into guest preferences and behaviors, facilitating the creation of highly targeted marketing campaigns. A comparative study of SVM algorithms with and without SMOTE demonstrated the significance of data balancing techniques, with accuracies of 85.19% and 93.86%, respectively. Additionally, integrating Oracle Apex for data visualization and decision support enhances strategic planning and operational efficiency. The findings highlight that the combined use of advanced data analytics and sophisticated digital tools leads to improved customer satisfaction, refined marketing strategies, and sustained competitive advantage, contributing to the overall growth and success of the hospitality sector.